Environmental exposure pathways of microplastics and their toxic effects on ecosystems and the nervous system - Lu, Kuo; Que, Yixiang; Wang, Longfei; Wang, Yanfan; Qiu, Jinyan; Jia, Yangyang; Ding, Cong; Wang, Dazhong; Cheng, Weyland; Zhang, Yaodong (Frontiers in Toxicology, 2025)
Microplastics are a troubling consequence of modern civilization, permeating ecosystems worldwide and posing a risk to both the environment and human health. As studies have revealed their extensive distribution throughout bodies of water, soil, and the atmosphere, the ecological crisis and health issues linked to microplastics have become a significant concern within the global scientific community. These tiny particles can enter the human body through various routes, including ingestion, inhalation, and even skin contact, and they have been shown to cross critical barriers such as the placental and blood–brain barriers. Their accumulation in the food chain disrupts the delicate balance of ecosystems and may impair cognitive function and behavioral patterns in living organisms. Alarmingly, there is increasing evidence suggesting that microscopic particles may contribute to the increasing rates of neurodegenerative diseases. This paper reviews the pathways through which microplastics are ingested, their effects on biological functions, and the potential mechanisms that contribute to their neurotoxicity. We emphasize the urgent need for further research to elucidate the toxicological impacts of microplastics and devise effective strategies for mitigating their effects on both ecosystems and human health.